2015
DOI: 10.1038/pr.2015.265
|View full text |Cite
|
Sign up to set email alerts
|

Meconium-induced inflammation and surfactant inactivation: specifics of molecular mechanisms

Abstract: This review summarizes neonatal meconium aspiration syndrome in light of meconium-induced inflammation and inflammatory surfactant inactivation, related to both endogenous and therapeutic exogenous surfactant. The wide effect of meconium on surfactant properties is divided into three points. Direct effect of meconium on surfactant properties refers mainly to fragmentation of dipalmitoylphosphatidylcholine and other surfactant phospholipids together with cleavage of surfactant proteins. Initiation of inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 97 publications
(128 reference statements)
0
34
0
Order By: Relevance
“…Various anti-inflammatory drugs (such as glucocorticoids, phosphodiesterase inhibitors, angiotensin-converting enzyme inhibitors, cyclooxygenase inhibitors, or antioxidants) have been tested as possible MAS therapies. [7][8][9][10][11] The therapeutic value of these anti-inflammatory agents in the management of MAS is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Various anti-inflammatory drugs (such as glucocorticoids, phosphodiesterase inhibitors, angiotensin-converting enzyme inhibitors, cyclooxygenase inhibitors, or antioxidants) have been tested as possible MAS therapies. [7][8][9][10][11] The therapeutic value of these anti-inflammatory agents in the management of MAS is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It also decreases the levels of surfactant proteins A and B and directly harms type II pneumocytes, thereby decreasing surfactant production. 15 In recent clinical trials, improved gas exchange following surfactant treatment was demonstrated in both term and preterm neonates with respiratory conditions other than surfactant deficient RDS, such as meconium aspiration syndrome, bacterial pneumonia and bronchopulmonary dysplasia. 16 Surfactant therapy in MAS is analysed by various researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Meconium-induced surfactant dysfunction is multilevel process, starting with direct effect of meconium on surfactant components and ending with harmful inflammatory and oxidative cascades (Kopincova and Calkovska 2016). Despite confirmed deleterious effect on endogenous surfactant, effectivity of exogenous surfactant given as in newborns with MAS is still discussed.…”
Section: Discussionmentioning
confidence: 99%
“…When we compared only Mec and Surf group using non-parametric Mann-Whitney U test, significance was marked, in accordance with our previous results, where surfactant treatment prevented oxidative damage in lung tissue and systemic circulation (Kopincová et al 2014, Mikolka et al 2016b. And finally, no change in apoptotic markers suggests that small amount of residual meconium is able to initiate inflammatory cascades which in turn activate each other (Kopincova and Calkovska 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation